A Compact Back-Plaster Sensor Node for Dementia and Alzheimer Patient Care - Schwarzmeier, Andre; Besser, J.; Weigel, Robert; Fischer, Georg; Kissinger, Dietmar (2014 IEEE Sensors Applications Symposium (SAS 2014), 2014)
Abstract— This paper presents a compact and highly integrated back-plaster sensor node equipped with seamless localization (in-door and out-door) using assisted GPS and bluetooth localization, activity classification and fall detection as well an GSM module providing a GPRS connection to a server infrastructure for supporting dementia and Alzheimer patients within their daily life. The innovative and durable design as a hermetic rubber-sealed, waterproof and sanitizable back-plaster ensures optimum wearing comfort for the patient as well as reliable fall-detection. In addition with an internet server infrastructure the described plaster sensor node allows to inform relatives or professional care staff in case of an emergency and help to enhance the quality of life by increasing the sense of feeling secure.
elib2cris::1512001600,schwarzmeier2014
Keywords: Index Terms— remote health monitoring; medical information system; fall-detection; localization; sensor processing; data fusion